Developing Gamified E-Worksheets for Reading Narrative Texts at UPT SMP Negeri 10 Medan - Pohan, Hammi Kasifa; Erlita, Yeni (Universitas Negeri Medan, 2025)
The purpose of this study is to develop a gamified e-worksheet for eighth-grade students at UPT SMP Negeri 10 Medan to help students comprehend narrative texts. This development is based on the Gamification of Learning and Instruction Theory (Kapp, 2012). The need for this product arose from students' difficulties in understanding narrative text, limited vocabulary, low motivation, and preference for interactive digital media. Using the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation), the researcher created e-worksheets that integrated game elements—such as storytelling, levels, competition, goals, rewards, and feedback—using Canva, Educaplay, and Genially platforms. Material and media expert validation gave an average score of 4.6 out of 5, or 93%, in the